Exploring the Changes in Code Status During the COVID-19 Pandemic and the Implications for Future Pandemic Care. (November 2022) - Katamreddy, Adarsh; Ye, Alexander M.; Vorchheimer, David A.; Hardoon, Isaac; Faillace, Robert T.; Taub, Cynthia C.
Objective: We aim to explore patterns of inpatient code status during the COVID-19 pandemic compared with a similar timeframe the previous year, as well as utilization of palliative care services. Methods: This is a retrospective cohort study using data from the Montefiore Health system of all inpatient admissions between March 15-May 31, 2019 and March 15-May 31, 2020. Univariate logistic regression was performed with full code status as the outcome. All statistically significant variables were included in the multivariable logistic regression. Results: The total number of admissions declined during the pandemic (16844 vs 11637). A lower proportion of patients had full code status during the pandemic (85.1% vs 94%, P < .001) at the time of discharge/death. There was a 20% relative increase in the number of palliative care consultations during the pandemic (12.2% vs 10.5%, P < .001). Intubated patients were less often full code (66.5% vs 82.2%, P < .001) during the pandemic. Although a lower portion of COVID-19 positive patients had a full code status compared with non-COVID patients (77.6% vs 92.4%, P<.001), there was no statistically significant difference in code status at death (38.3% vs 38.3%, P = .96). Conclusions: The proportion of full code patients was significantly lower during the pandemic. Age and COVID status were the key determinants of code status during the pandemic. There was a higher demand for palliative care services during the pandemic.